ADDRESS TERMS USED BY ONLINE SHOP SELLERS TO THEIR FEMALE TEENAGE CUSTOMERS AND YOUNG MOTHER CUSTOMERS IN FACEBOOK - Deviani S. Anggrawan; Herwindy Maria Tedjaatmadja (Institute of Research and Community Outreach - Petra Christian University, 2013)
This study is about address terms used by online shop sellers to female teenage and young mother customers as well as their similarities and differences in Facebook. It is supported by theories of address terms by Crystal (2009), Kuntjara (2012), Wardhaugh (2006), and Holmes (2001). She observed eight online shops, four for female teenagers and four for young mothers, ten comments from each shop. The finding reveals three types of address terms were used to female teenagers and five types of address terms were used to young mothers. The similarities are all address terms are female type address terms; formal name did not occur; and several same address terms types occurred in both types of shops. The differences are kinship terms variation in online shops for female teenagers and young mothers; intimate name and other types occurred in online shops for young mothers; and the frequency of each type.